The Demise of the Left Parties in Israel: From Party Identification to a Negative Partisanship - Levy Mordechai (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The left parties are the oldest political institutions in Israel. They were founded before the establishment of the State and were the dominant political force in its first decades. However, since the 1990s, there has been a consistent decline in their power, to the point where, in the last Knesset elections held in 2022, the left parties barely passed the threshold. This article explains the decline of the left parties and attempts to answer where the voters went. A combination of several local and global events that occurred in recent years caused the left parties to distance themselves from the narrative of Zionist Socialism characterizing them and to adopt a new narrative, which less inspires identification of Jewish voters. The article’s main argument is that the voters did not disappear but only changed their political behavior from a state of party identification and voting for the left parties to a state of political opposition and voting against the rightist parties. To illustrate the pattern of behavior, voting data for the Knesset in two communities with different demographic characteristics are presented: Kibbutz Mizra, a socialist commune identified with left voters, and Beit-Shean, a town that is a stronghold of rightist voters. The conclusion is that the way for the left parties to return to dominance is through reintegrating the Jewish identity with the values of justice and equality. Partie lewicowe są najstarszymi instytucjami politycznymi w Izraelu. Powstały przed utworzeniem państwa i były dominującą siłą polityczną w pierwszych dziesięcioleciach jego istnienia. Jednak od lat 90. XX w. następuje systematyczny spadek ich władzy do tego stopnia, że w ostatnich wyborach do Knesetu, które odbyły się w 2022 r., partie lewicowe ledwo przekroczyły próg. Artykuł wyjaśnia upadek partii lewicowych i próbuje odpowiedzieć, dokąd poszli wyborcy. Splot kilku wydarzeń o charakterze lokalnym i globalnym, jakie miały miejsce w ostatnich latach, spowodował, że partie lewicowe zdystansowały się od charakteryzującej je narracji o syjonistycznym socjalizmie i przyjęły nową narrację, w mniejszym stopniu inspirującą do identyfikacji żydowskich wyborców. Głównym argumentem artykułu jest to, że wyborcy nie zniknęli, a jedynie zmienili swoje zachowania polityczne ze stanu identyfikacji partyjnej i głosowania na partie lewicowe do stanu opozycji politycznej i głosowania przeciwko partiom prawicowym. Aby zilustrować schemat zachowań, zaprezentowano dane dotyczące głosowania w Knesecie w dwóch społecznościach o różnej charakterystyce demograficznej: kibucu Mizra – gminie socjalistycznej utożsamianej z wyborcami lewicy oraz Beit-Shean – mieście będącym bastionem wyborców prawicy. Wniosek jest taki, że sposobem na powrót partii lewicowych do dominacji jest reintegracja tożsamości żydowskiej z wartościami sprawiedliwości i równości.
Upadek partii lewicowych w Izraelu: od identyfikacji partii do negatywnej stronniczości
Keywords: Israel; left parties; electoral volatility; political narrative; party identification; negative partisanship; Izrael; partie lewicowe; zmienność wyborcza; narracja polityczna; identyfikacja partyjna; negatywna stronniczość